2011
DOI: 10.1111/j.1526-100x.2011.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Fish and Benthic Macroinvertebrate Diversity of Restored Urban Streams to Reference Streams

Abstract: Urbanization is associated with substantial losses to stream biological diversity throughout the United States' midAtlantic. Stream restoration has been used to improve stream conditions and, in part, to ameliorate these losses. However, the relationship between restoration and recovery of biological diversity is unclear. Our objective was to critically examine the efficacy of urban stream restorations with regard to biological diversity. We compared restored urban streams to urban nonrestored, nonurban, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 43 publications
3
63
0
Order By: Relevance
“…The negative impact of such factors on biological diversity of benthic invertebrates in freshwater environments is frequently assumed in numerous studies (e.g. Reice, 1985;Lorenz et al, 2004;Sánchez-Montoya et al, 2010;Stranko et al, 2012), but the lack of such direct effects was also found (e.g. Heino et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The negative impact of such factors on biological diversity of benthic invertebrates in freshwater environments is frequently assumed in numerous studies (e.g. Reice, 1985;Lorenz et al, 2004;Sánchez-Montoya et al, 2010;Stranko et al, 2012), but the lack of such direct effects was also found (e.g. Heino et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results presented in this paper require replication, especially in terms of additional sampling of the same river stretches over time (months or years after dredging was implemented), and extension to other elements of the riverine environment in order to provide a comprehensive analysis of rivers' responses to dredging [22]. Extension of the research to, for example, the response of fish communities to dredging-induced changes in mesohabitat structure and macroinvertebrate composition would allow results to reveal the relevance of the maintenance of agricultural rivers to fishery management [23,24]. Research on these aspects is now ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Case studies have typically emphasized the poor success in achieving measurable biological gains solely through manipulation of physical habitat, particularly in the absence of any broader analysis of whether that habitat is truly limiting from a population perspective. Such outcomes have been reported from a variety of locations and watershed contexts, particularly channels in highly disturbed urban watersheds where altered flow regimes and water chemistry are typically as or more impacted than physical habitat (e.g., [6][7][8][9][10][11]; Figure 1). In less disturbed watershed settings, results are commonly more biologically successful, but rarely do they approach full recovery of the instream and biological conditions found in fully undisturbed settings (e.g., [12][13][14][15][16][17][18]).…”
Section: Limiting-factors Analysismentioning
confidence: 99%